Analisis Kualitas Air Akibat Keramba Jaring Apung Di Danau Toba Dusun Sualan Desa Sibaganding Kabupaten Simalungun Sumatera Utara - Sudoyo Lumban Tobing; Ternala Alexander Barus; Desrita Desrita (AQUACOASTMARINE, 2014)
Sualan hamlet of Sibaganding Village is one of the territorial waters Lake Toba which used for floating nets activity. Floating nets aquaculture activities can affect the water quality Lake Toba in the hamlet of Sualan. This research aims to know the water quality based on physical and chemical parameters. Physical and chemical parameters the water analyzed by the storet method. The Research was starting from April up to May 2014. The research method used was Purposive Random Sampling. There are station I (Keramba), station II (Transition), and Station III (control). The value of physical and chemical parameters such as temperature 26,00 ºC – 28,00 ºC, turbidity (TSS) 0,89 – 5,21 mg/l, DO 5,41 – 8, 24 mg/l, pH 6,40 − 7,30, BOD 7,30 – 6,40 0,59 – 1,27 mg/l, nitrate 0,69 – 2,10 mg/l, phosphate 0,11 – 0,28 mg/l. According to physical and chemical parameters of water quality for the first station refers to third class. While on the second and the third station are refers to first class.Keywords: Water quality, Floating nets, Lake Toba